Second-order multi-objective non–differentiable Schaible type model and its duality relation under (K xQ)–C–type–I functions. (3rd September 2021) - Kumar, Rajnish; Alam, Khursheed; Dubey, Ramu
ABSTRACT: In this article, we constructed second-order ( K × Q ) - C -type-I functions and also illustrated a non-trivial concrete numerical example for such existing types of functions. Furthermore, we have presented a second-order non-differentiable multi-objective Schaible type dual model with cone objectives as well as cone constraints. Finally, we established duality theorems under ( K × Q ) - C -type-I assumptions.